Learning capability and work experience to employee loyalty: moderation effect of resilience to change - Pratama, Tegar; Pujianto, Wahyu Eko (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
This research explains the effect of learning capability to work experience and employee loyality: Moderation effect resilience to change. This research is survey research using to the technique of distributing questionnaires to the sample used in this research of 85 pouple, the hypothesis was tested using Partial Least Square with SmartPLS 4.0 Software. Variable measurement uses a Likert scale of 1 to 5. Thaat results of this study show that: (1) tihere is a significanti positiive influence of learning capabilitiy on work experience. (2) tihere is a significanti positiive influence of learning capability on employee loyality. (3) tihere is a significanti positiive influence of work experience in employee loyality. (4) tihere is a significanti influence of resilience to change on work experience. (5) tihere is a significanti positiive influence of resilience to change o employee loyality.(6) there is a insignificant negative influence of resilence to change on learning capability and work experience.(7) there is a insignificant negative effect of resilience to change on learning capability and employee loyality.